2019
DOI: 10.3390/ijerph16091616
|View full text |Cite
|
Sign up to set email alerts
|

Can Forum Play Contribute to Counteracting Abuse in Health Care? A Pilot Intervention Study in Sri Lanka

Abstract: Obstetric violence refers to the mistreatment of women in pregnancy and childbirth care by their health providers. It is linked to poor quality of care, lack of trust in health systems, and adverse maternal and neonatal outcomes. Evidence of interventions to reduce and prevent obstetric violence is limited. We developed a training intervention using a participatory theatre technique called Forum Play inspired by the Theatre of the Oppressed for health providers in Sri Lanka. This paper assesses the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Our results are consistent with research confirming that role-playing is an effective way to enhance empathy and to improve the communication skills of health professionals [ 29 , 30 ]. They also support the findings that showed that participants in FP workshops had experienced a change in their motivation and perceived ability to act in situations of AHC [ 31 , 32 , 33 ]. However, while these studies gave reason to assume that FP workshop training increased the awareness of AHC as a shared problem, such a change could not be seen in the quantitative evaluation presented in this article.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with research confirming that role-playing is an effective way to enhance empathy and to improve the communication skills of health professionals [ 29 , 30 ]. They also support the findings that showed that participants in FP workshops had experienced a change in their motivation and perceived ability to act in situations of AHC [ 31 , 32 , 33 ]. However, while these studies gave reason to assume that FP workshop training increased the awareness of AHC as a shared problem, such a change could not be seen in the quantitative evaluation presented in this article.…”
Section: Discussionsupporting
confidence: 82%
“…In Sri Lanka, multi-professional teams provide maternity care; in our study setting, physicians and registered nurses are the primary health providers during childbirth. Twenty physicians and 30 nurses participated in the workshops [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 is an example of one of the situations of AHC identified by the participants based on personal experiences that we explored in a workshop. Our prior publication on this pilot intervention contains an additional example and further details about the methodology [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence shows that the implementation of specialized respectful maternity care programs and interventions that positively in uence the attitude and response of maternity care providers are generally effective in reducing the rate of mistreatment of childbearing women during intrapartum care services in developing countries [9][10][11][12][13][14][15]. Some of these programs and interventions include theatrebased training interventions to reduce obstetric violence [14], monitoring of midwives during practice [9], improvement in working conditions of healthcare providers [11], equipping midwives with the ability to identify and manage obstetric and neonatal emergencies [16], and the training of midwives to effectively communicate with clients [10,17].…”
Section: Introductionmentioning
confidence: 99%